Temperature evolution of magnetic properties for (Cu/Co)(60)/Fe multilayer - (:unkn) unknown (ELSEVIER, 2015)
In order to investigate the magnetic properties by ferromagnetic resonance (FMR) techniques, (Cu/Co)(60)/ Fe multilayer on Si(001) substrate has been prepared by conventional sputtering. Evolution of the FMR spectra with temperature, resonance field, and magnetization curve has been calculated using the Lanclau-Lifshitz equation of motion for magnetization with the Bloch-Bloembergen type damping term. An almost linear evolution of frequency of resonance field has been shown for x-, k- and q-band spectra. By the analysis of the resonance field-frequency relation, the effect of the internal field is refined and thus the spectroscopic g-value and internal field were calculated. The magnetostatic signal originated from the magnetostatic anisotropy energy has been determined to be opposed by the decreasing exchange and dipolar energies. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Multilayer film; Low temperature FMR study; Magnetic property; Magnetostatic anisotropy energy; Spin-orbit interaction; FERROMAGNETIC-RESONANCE; SURFACE ANISOTROPY; THICKNESS DEPENDENCE; FILMS; FMR; MAGNETORESISTANCE; MAGNETOIMPEDANCE; ABSORPTION; SCATTERING; MODES